An epidemic of pseudomembranous colitis: importance of person to person spread. Issue 11 (November 1987) - Nolan, N P; Kelly, C P; Humphreys, J F; Cooney, C; O'Connor, R; Walsh, T N; Weir, D G; O'Briain, D S
Abstract : Twenty three cases of pseudomembranous colitis (PMC) occurred in three hospitals in 10 months. Retrospective analysis shows that they represented a single epidemic with a readily traceable chain of person-to-person contact within and between hospitals. Most patients had severe pre-existing illness and all had broad spectrum antibiotics, including either ampicillin/amoxycillin, a broad spectrum cephalosporin (particularly cefotaxime), or both. All patients had severe diarrhoea and all responded to vancomycin, but relapse occurred in five. Ten patients eventually died, principally because of underlying disease rather than from PMC. Failure to find fibrin thrombi in blood vessels in biopsies and the scanty distribution of non-invasive bacteria supports the concept of mucosal damage by bacterial toxin, rather than by direct infection, or ischaemia. Although environmental colonisation cannot be excluded, the observed pattern of spread suggests a major role for direct person-to-person crossinfection in the spread of disease in this outbreak.